Spermatogonial fate in mice with increased activin A bioactivity and testicular somatic cell tumours - Whiley, Penny A. F.; Nathaniel, Benedict; Stanton, Peter G.; Hobbs, Robin M.; Loveland, Kate L. (Frontiers in Cell and Developmental Biology, 2023)
Adult male fertility depends on spermatogonial stem cells (SSCs) which undergo either selfrenewal or differentiation in response to microenvironmental signals. Activin A acts on Sertoli and Leydig cells to regulate key aspects of testis development and function throughout life, including steroid production. Recognising that activin A levels are elevated in many pathophysiological conditions, this study investigates effects of this growth factor on the niche that determines spermatogonial fate. Although activin A can promote differentiation of isolated spermatogonia in vitro, the impacts on SSC and spermatogonial function in vivo is unknown. To assess this, we examined testes of Inha KO mice, which feature elevated activin A levels and bioactivity and develop gonadal stromal cell tumours as adults. The GFRA1+ SSCenriched population was more abundant and proliferative in Inha KO compared to wildtype controls, suggesting that chronic elevation of activin A promotes a niche which supports SSC self-renewal. Intriguingly, clusters of GFRA1+/EOMES+/LIN28A-cells, resembling a primitive SSC subset, were frequently observed in tubules adjacent to tumour regions. Transcriptional analyses of Inha KO tumours, tubules adjacent to tumours, and tubules distant from tumour regions, revealed disrupted gene expression in each KO group increased in parallel with tumour proximity. Modest transcriptional changes were documented in Inha KO tubules with complete spermatogenesis. Importantly, tumours displaying upregulation of activin responsive genes, were also enriched for factors that promote SSC self-renewal, including Gdnf, Igf1, and Fgf2, indicating the tumours generate a supportive microenvironment for SSCs. Tumour cells featured some characteristics of adult Sertoli cells but lacked consistent SOX9 expression and exhibited an enhanced steroidogenic phenotype, which could arise from maintenance or acquisition of a fetal cell identity or acquisition of another somatic phenotype. Tumour regions were also heavily infiltrated with endothelial, peritubular myoid and immune cells, which may contribute to adjacent SSC support. Our data show for the first time that chronically elevated activin A affects SSC fate in vivo. The discovery that testis stromal tumours in the Inha KO mouse create a microenvironment that supports SSC selfrenewal but not differentiation offers a strategy for identifying pathways that improve spermatogonial propagation in vitro.